PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA POLA SWADAYA DI DESA SIMPANG TIGA KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Gultom, Fernando; Yulida, Roza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are 1) to know the implementation of extension, 2) to know the role extension agent to increase the empowerment ofcoconut self-supporting farmer. This research used survey method. The samples in this research used purposive sampling method with criteria of land area at least 2 hectares, who has joined in farmer group and has over 7 years of farm experience. Data analysis useddescriptive and Scale Likert's Summated Rating (SLSR).The results showed that the implementation of extension in Simpang Tiga Village didn’t go well. The role of extension included in